The impact of urate-lowering therapy on kidney function (IMPULsKF) - Ivanov, D.D. (KIDNEYS, 2021)
The concept of trial launched in Ukraine in 2017 with POEM design and 36-months duration is presented. It aims to investigate the impact of two target levels of urate-lowering therapy caused by hyperuricemia on kidney function and chronic kidney disease (CKD) progression measured by estimated glomerular filtration rate and albuminuria in 180 patients with gout (n = 90) and with CKD (n = 90). The main current tasks include: 1) evaluation of serum urate acid (SUA) level most potential preserving kidney function; 2) the new onset of gout attacks depending on SUA level, both in gout and CKD objects; 3) safety and side effects of target and ultra-low SUA levels for evidence-based urate-lowering therapy optimal regime in CKD and non-CKD with gout.